Contrasting innovation dynamics of professional-technological knowledge intensive business services in metropolitan areas - Şahin, Mehmet Tahsin; Niemets, Liudmyla; Yilmaz, Mutlu; Kliuchko, Liudmyla; Varol, Çiğdem (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Formulation of the problem. The study examines knowledge-intensive business services (KIBS) firms’ capability to access, process, and transform information into innovation. KIBS are defined as facilitators, carriers of knowledge, and sources of innovation for other sectors. KIBS play an important role in the production, use, and transfer of knowledge to the manufacturing sector. KIBS activities do not demonstrate a uniform structure within themselves, so a dual classification as professional services (P-KIBS) and technological services (T-KIBS) based on functioning and input has been developed. KIBS activities are concentrated in large cities. Major cities or capitals have well-developed infrastructure, public administration centers, advanced social activities, and numerous research institutes and universities. All of them attract a highly skilled population. Regarding metropolitan city economic growth, KIBS stand out because of their high added value, high income, high innovation returns, and high financial capacity, and they contribute to development. The purpose. The present study aims to reveal the innovative capacities and dynamics of P-KIBS and T-KIBS firms operating in the metropolitan area of Ankara, Turkey’s capital city. To reach this aim, Turkey’s capital city Ankara is analyzed by using the results of a questionnaire applied to 410 small and medium-sized (SMEs) KIBS firms, 146 of which are P-KIBS firms and other 264 are T-KIBS firms. Methods. In the course of the research and preparation of the article, the authors used several scientific methods, both philosophical and general scientific, as well as specific scientific methods. In particular, the methods of analysis and synthesis, induction and hypothetical-deductive method, mathematical-statistical and spatial analysis, methods of grouping and classification, questionnaires and surveys, etc., were used. The results. There are notable differences between the P-KIBS and T-KIBS firms, considering their spatial distribution patterns and the dynamics of their innovation processes. The spatial distribution patterns of the KIBS firms were revealed. While T-KIBS activities demonstrate a spatial clustering tendency independent of the CBD, the P-KIBS firms prefer to locate within the CBD or its vicinity. KIBS sectors generally prefer to be situated by high-income residents, new settlements, secure and prestigious areas close to large public institutions such as ministries and general directorates. It was revealed that the T-KIBS firms are most densely located in the CBD and newly developing business districts of Balgat and Söğütözü, and in the Technology Development Zones of Ankara. P-KIBS firms, on the other hand, are more widely spread in the Çankaya and Yenimahalle districts. It was found that advances in information and communication technologies have a varied impact on the location selection preferences of P-KIBS and T-KIBS enterprises. According to the research results, the factors influencing the clustering of P-KIBS companies and T-KIBS firms were identified and determined. There is a significant relationship between the innovative P-KIBS and T-KIBS firms and their collaboration with other institutions. As a result of the the study, it has been determined that there is a significant relationship between collaboration, R&D, intrafirm and extrafirm social relationships on the innovation of KIBS firms and also contrasting innovation dynamics related to different classes of KIBS in metropolitan areas.